EVALUASI PEMBELAJARAN IPA DI SEKOLAH MENENGAH PERTAMA NEGERI 4 MEMPAWAH HILIR - Ratna Sari Amalia; Aloysius Mering; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to evaluate the science learning program in State Junior High School 4 (SMP Negeri 4) Mempawah Hilir in terms of facilities, process and product based on the Regulation of Minister of Education and Culture of the Republic of Indonesia Number 24 of 20=07 and No 22 and 23 of 2016 concerning the facilities and infrastructures, the standard process and standard assessment on primary and secondary education. This research is an evaluation research using discrepancy model. Data collection was carried out using observation, questionnaire, interview and documentation techniques. The conclusions of this study are, as follow : the facilities evaluation is in the good category, the process evaluation is in the very good category and the product evaluation is in the good category. In general, the results evaluation shows that the science learning in SMP Negeri 4 Mempawah were in the good category.Keywords : Evaluation, Sciences Learning, Discrepancy Model